Metacognition Profile of Vocational High School Students in Mathematics Problem Solving Based on Logical Thinking Skills - Mu'jizatin Fadiana; Andriani Andriani (STAI Hubbulwathan Duri, 2021)
This study describes the profile of vocational high school students' metacognitive abilities in mathematics problem solving based on their logical thinking abilities. This research was conducted using descriptive research methods with a qualitative approach. The data was collected using a logical thinking ability test and problem-solving test and. Three students were selected who met different logical thinking stages: the abstract operation stage, the transition stage, and the concrete operational stage. The results showed the subject of the abstract operation stage fulfilled the metacognition stage by re-describing the given problem, knowing the relationship between what was known and what was asked, working on the problem by writing down what was known and asked and entering into the formula and also checking the answer. Transition stage subjects fulfill the metacognition stage by describing initial information and instructions, performing problem-solving steps, and counting to check completed work. The subject of concrete operations fulfills the metacognition stage by stating information and instructions that are non-specific and detailed. The subject has not been able to state the proper steps to ensure the information's conformity with the problem, and the subject sees what is done by calculating.